2008
DOI: 10.2514/1.29862
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Model of Drosophila Flight

Abstract: This paper presents a framework for simulating the flight dynamics and control strategies of the fruit fly Drosophila melanogaster. The framework consists of five main components: an articulated rigid-body simulation, a model of the aerodynamic forces and moments, a sensory systems model, a control model, and an environment model. In the rigid-body simulation the fly is represented by a system of three rigid bodies connected by a pair of actuated ball joints. At each instant of the simulation, the aerodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(140 citation statements)
references
References 59 publications
7
133
0
Order By: Relevance
“…S2A). This value is reasonably close to the value for total system drag (8.0 μN·s·m −1 ) predicted from a detailed quasi-steady model of flapping flight simulated in forward motion (6) (Fig. 3C).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…S2A). This value is reasonably close to the value for total system drag (8.0 μN·s·m −1 ) predicted from a detailed quasi-steady model of flapping flight simulated in forward motion (6) (Fig. 3C).…”
Section: Resultssupporting
confidence: 86%
“…This multimodal feedback enables them to perform aerial feats, such as chasing conspecifics (3) and rapid self-righting after takeoff (4). Our neurobiological and biomechanical understanding of these behaviors is incomplete, but physiological studies and physics-based models have helped reveal salient features (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…We chose a frictional drag model as opposed to a turbulent drag model because of the comparatively low Reynolds number, which was in the order of 100 for the highest body velocities (using 3 mm as the characteristic length). We also considered the damping on the flapping wings during vertical translation based on a quasi-steady aerodynamic model of the wing forces and empirically measured force coefficients (Sane & Dickinson 2002;Dickson et al 2008). This analysis (also see Mronz & Lehmann 2008;Hedrick et al 2009;Cheng et al 2010) revealed that the wing damping depends linearly on the vertical speed of the fly (data not shown).…”
Section: Validity Of Inertial Modelmentioning
confidence: 99%
“…System identification techniques (applied to flight control in the fruitfly, e.g. Epstein et al 2007, Dickson et al 2008Fry 2009;Rohrseitz & Fry submitted) provide a solid analytical framework based on rigorous engineering principles. Such a system analysis does not require a detailed understanding of the highly complex and only partially understood neuromotor control mechanisms underlying the studied reflex.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is that the assumption of uniform distribution about non-dimensional chordwise location of COP for translational and rotational circulation aerodynamic mechanism is introduced to simplify the calculation of rotational aerodynamic moment. Because of the difficulty of direct measurements of rotational moments and the lack of exploring possible chordwise location of COP of rotational circulation aerodynamic mechanism [8,40,47,48], the calculation of rotational aerodynamic moment is either neglected [25] or consciously executed by assumption that the chordwise position distribution of COP for aerodynamic force arising from translational and rotational circulation is identical, and located at the geometric center of the wing strip elements [8,40].…”
Section: Aerodynamic Momentsmentioning
confidence: 99%